Pemberdayaan Siswa dan Siswi dalam Pemanfaatan Kecerdasan Buatan (AI) secara Etis dan Produktif di Lingkungan Sekolah - Dina Atika Hesti; Grimonia Ozora; Venti Mayranda Silalahi; Yulia Hanoselina; Rahmadhona Fitri Helmi (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
This research aims to examine the strategies for empowering students in using artificial intelligence (AI) ethically and productively in the school environment. The background of this research is based on the increasing use of AI technology by students, but it has not been accompanied by an understanding of ethical values and social responsibility. This study uses a literature study method with a qualitative approach through thematic analysis of various relevant scientific sources in the last five years. The results show that the use of AI can improve students' creativity, digital literacy, and 21st century skills when accompanied by training and strengthening moral values. The role of teachers, an adaptive curriculum, and ethics-based education policies are key factors in encouraging the responsible use of AI. This study concludes that student empowerment in the use of AI is not only a technical aspect, but also an effort to build character and critical awareness of technology. The implications of this research are expected to contribute to the development of learning models that are relevant to the challenges of the digital era and provide policy direction for educational institutions.